Three-dimensional observation of magnetic fields in alloy tool steel under spherical Hertzian contact. (March 2014) - Kida, K.; Uryu, M.; Honda, T.; Santos, E. C.; Saruwatari, K.
Abstract : Failure of dies and moulds is caused by wear and deformation during the metal sheet forming process. Die wear takes various forms, and the contact conditions in die parts affect the strength of the components. Non-destructive evaluation methods that can be related to contact conditions are necessary to study and understand the phenomena caused by the contact stresses. In the present work, a newly developed scanning Hall probe microscope (SHPM) equipped with a GaAs film sensor was used to observe the three-dimensional magnetic fields in tool steel plates before and after contact tests at room temperature in air. Around the contact test area, changes in 'S' and 'N' poles generated by magnetisation using a square magnet block were investigated. It was found that the intensity of three-dimensional magnetic fields is only slightly affected by the spherical Hertzian contact. However, all of the three-dimensional components of the magnetic fields change significantly. The extent of the changes depends not on the distribution of stress under spherical Hertzian contact, but on the initial distribution of the magnetic fields.